If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 5y + -1x = 0 Reorder the terms: 15 + -1x + 5y = 0 Solving 15 + -1x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -1x + -15 + 5y = 0 + -15 Reorder the terms: 15 + -15 + -1x + 5y = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -1x + 5y = 0 + -15 -1x + 5y = 0 + -15 Combine like terms: 0 + -15 = -15 -1x + 5y = -15 Add '-5y' to each side of the equation. -1x + 5y + -5y = -15 + -5y Combine like terms: 5y + -5y = 0 -1x + 0 = -15 + -5y -1x = -15 + -5y Divide each side by '-1'. x = 15 + 5y Simplifying x = 15 + 5y
| 3z-30+6z=10z-50 | | 180x^2-125y^2=0 | | -14+t=37 | | 4=-2y-3x | | f=1.8(20)+32 | | 18-6y=-10x | | 0=X^4-2x^3-98x^2+200x-300 | | 4(3+2x)-5=15 | | 5(x+9)=-3(21+x) | | -4x-6-3x=4 | | 3=9-2x | | 9x^2+121=0 | | x^12=32 | | 19x+16=4(7+x)+3 | | 19x+16=4(7+x) | | 8+4s=16 | | 4x+110=x^2+x | | 12x=0.5 | | (3/4x+2)-(1/4x+5)= | | 12x-4y=3 | | Cos(3x)=-2cosx | | (12a^2b+8a-5a^2b+2ab)-(4ab^2+6ab-2a-3ab)= | | x(x+1)-x=2x^2 | | 2x+11=5x+32 | | (3x-2)(4x-14)=0 | | (3x-2)(4x-4)=0 | | Solve-5w=-80forw | | 3k+23=13 | | (2x-x)(4x-14)=0 | | x+x^2=2x^2 | | 3(g-2)=2(10+g) | | Y=1.5x-6 |